Association of Helicobacter pylori and intestinal parasites in the stool samples of patients with dyspeptic complaints (Annals of Medical Research, 2024)
Aim: Helicobacter pylori and infections due to intestinal parasites are quite common in developing countries around the world, in societies with low socioeconomic levels, and in regions with inadequate and unhealthy drinking water and food. Our study aimed to reveal the association  Helicobacter pylori positivity and intestinal parasites (IP) in the stool patients who came to the hospital due to dyspeptic complaints.Materials and Methods: Between 01.2018 and 04.2024, 953 patients admitted to the hospital with dyspepsia and whose stool samples were taken were examined. The data of patients for whom stool Helicobacter pylori rapid antigen test, IP test and demographic variables were requested were evaluated retrospectively.Results: Of the 953 patients, 396 (41.6%) were male and 557 (58.4%) were female. Patient ages ranged from 18 to 85 years and the average was 38.65∓15,15.64 years. The patients were divided into two age groups. There were 882 (92.5%) patients between the ages of 18-65, and 71 (7.5%) patients between the ages of 66-85. Entamoeba histolytica (E. histolytica) / Entamoeba dispar (E. dispar) in 12 (1.3%) of the patients, Giardia intestinalis (G. intestinalis) in 24 (2.5%), Blastocystis hominis (B. Hominis) in 3 (0.3%) and H. pylori was detected in 128 (13.4%). The relationship between H. pylori and IP was found to be statistically significant. IP was detected in 20.3% of cases in which H. pylori was detected. No relationship was found between gender and H. pylori and IP. No relationship was found between age groups and H. pylori and IP.Conclusion: H. pylori and IP are found quite frequently in the world. To better understand the association between them, more comprehensive multi-center studies are needed, in which high-sensitivity methods are used and data can be compared with healthy control groups.
Keywords: Helicobacter pylori; Intestinal parasites; Giardiasis